A comparison between dexlansoprazole modified release–based and lansoprazole-based nonbismuth quadruple (concomitant) therapy for first-line Helicobacter pylori eradication: a prospective randomized trial - Tai, Wei-Chen (Infect Drug Resist, 2019)
PURPOSE: Steadily maintaining high intra-gastric PH is the major factor for successful Helicobacter pylori (H.pylori) eradication. It is important to search for a stronger PPI. Dexlansoprazole MR is a dual delayed release formulation PPI taken once daily which is capable of maintaining longer duration of high intra-gastric PH. It is very effective in treating gastroesophageal disease but reports on H, pylori eradication is very rare. This study sought to compare dexlansoprazole MR-based concomitant treatment and lansoprazole-based concomitant treatment in H. pylori infection and to investigate the factors that affect the eradication rates. METHODS: Two hundred two participants with H. pylori infection were included and randomly assigned to seven days of dexlansoprazole MR-based concomitant therapy (dexlansoprazole MR 60 mg once daily, clarithromycin 500 mg twice daily, amoxicillin 1 g twice daily and metronidazole 500 mg twice daily; DACM group) or a seven days of lansoprazole-based concomitant therapy (lansoprazole 30 mg twice daily, clarithromycin 500 mg twice daily, amoxicillin 1 g twice daily, and metronidazole 500 mg twice daily; LACM group). The participants were asked to perform urea breath tests eight weeks later. RESULTS: The eradication rates in the DACM group were 86.1% [95% confidence interval (CI): 77.8%–92.2%] in the ITT analysis and 90.6% (95% CI: 82.9%–95.6%) in the PP analysis, respectively, as compared with 90.1% (95% CI: 82.6%–95.2%) and 92.6% (95% CI: 85.5%–96.9%) (p=0.384 and p=0.572, respectively) in the LACM group for the same analyses. The adverse event rates were 11.5% in the DACM group and 10.2% in the LACM group (p=0.779). CONCLUSION: As a first-line H. pylori treatment regimen, dexlansoprazole MR-based concomitant therapy attained a successful eradication rate of 90%, which was non inferior to that of lansoprazole-based concomitant treatment. CLINICALTRIALS.GOV IDENTIFIER: NCT03829150.